Impact of lymph node status in patients with intrahepatic cholangiocarcinoma treated by major hepatectomy: a review of the National Cancer Database. Issue 1 (January 2016) - Jutric, Zeljka; Johnston, W. Cory; Hoen, Helena M.; Newell, Pippa H.; Cassera, Maria A.; Hammill, Chet W.; Wolf, Ronald F.; Hansen, Paul D.
Abstract: Introduction: Routine lymphadenectomy in the surgical treatment of intrahepatic cholangiocarcinoma (ICC) is not routinely performed. We aim to define predictive indicators of survival in patients with positive lymph nodes. Methods: The National Cancer Data Base (NCDB) was queried for patients who underwent major hepatectomy for ICC between 1998 and 2011. Clinical and pathologic data were assessed using uni- and multi-variate analyses. A sub-analysis was performed on the 160 patients with positive lymph nodes. Results: Of 849 patients with lymph node data, 57% had at least one lymph node examined. Median survival for lymph node negative patients was 37 months versus 15 months for lymph node positive patients. In lymph node positive patients, poorer survival was associated with not receiving chemotherapy (HR 1.83, p = 0.003), tumor size > 5 cm (p = 0.029), and older age (p < 0.0001). Lymph node positive patients age less than 45 had a median survival of 27 months. Conclusions: Overall survival in patients with lymph node metastases from ICC is poor. Adjuvant therapy was associated with a longer survival in lymph node positive patients, although prospective data are needed. Routine lymphadenectomy should be strongly considered to provide prognostic information and guidance for adjuvant therapy.